2017
DOI: 10.1116/1.4976003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc oxide film morphologies on the formation of Shewanella putrefaciens biofilm

Abstract: Zinc oxide (ZnO) films were prepared on aluminum substrate by a hydrothermal method to investigate the effect of their surface characteristics, including morphology and hydrophobicity, on the corresponding antibiofilm performance. The surface characteristics of the prepared ZnO films were examined by a comprehensive range of methodologies, suggesting that films of distinctive surface morphologies were successfully formed. Subsequently, their antibiofilm activities, using Shewanella putrefaciens as a model bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…Meanwhile, more biofilm adhesive materials nourish the biofilm bacteria, and the biofilm bacteria multiply rapidly. Consistent with our research, the biofilm adherence is inhibited by the higher hydrophobicity of ZnO film in the initial stage of the biofilm formation [ 49 ]. The adherence of biofilms is affected by the hydrophobic and hydrophilic properties of the materials [ 14 , 53 , 54 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, more biofilm adhesive materials nourish the biofilm bacteria, and the biofilm bacteria multiply rapidly. Consistent with our research, the biofilm adherence is inhibited by the higher hydrophobicity of ZnO film in the initial stage of the biofilm formation [ 49 ]. The adherence of biofilms is affected by the hydrophobic and hydrophilic properties of the materials [ 14 , 53 , 54 ].…”
Section: Resultssupporting
confidence: 91%
“…Chi et al [ 47 ] reported that anodized aluminum has no antibacterial activity to Gram-negative bacteria( Escherichia coli and P. aeruginosa ) and Gram-positive bacteria ( Streptococcus faecalis and Staphylococcus aureus ). However, ZnO has an excellent antibacterial and antibiofilm activity [ 25 – 27 ], and there is a positive correlation between antibacterial and antibiofilm activity [ 48 , 49 ]. Furthermore, the antibacterial properties of ZnO are affected by its microstructure [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…15 The same sharp nanorods with tip diameters of less than 10 nm exerted considerable pressure (up to 10 MPa) on the outer cell wall of bacteria when continuously mixed in solution. 16 Elsewhere, ZnO films composed of nanoscopic needles exhibited greater potential to inhibit bacteria biofilm formation compared to micron-length flakes, 17 and the surface broadness and protrusion of petals in flower-like formations were considered responsible for the differences observed in the antibacterial effect of ZnO structures. 18 ZnO nanoparticles composed of many individual nanosized needle clusters have been synthesized via the hydrothermal growth technique that have a typical crystal wurtzite structure and high purity.…”
Section: Introductionmentioning
confidence: 99%
“…Column 2 comments on the type of the surface that was created. For example, the materials are commonly used in the form of thin films [98,99,[129][130][131][132][133]100,103,104,[124][125][126][127][128] nanopatterned fiber, [134][135][136] nanopowder, [137,138] or nanorod [139,140] coatings on various test substrates (i.e., glass, steel, and specific polymers).…”
Section: Inorganic Materials Interacting With Microorganismsmentioning
confidence: 99%
“…At the same time, in certain cases the summary was broader, and a wide set of biointerface or microorganism characteristics were obtained. [98,[109][110][111]124,150,151] The most common inorganic materials used in biointerfacial structures are metal oxides such as ZnO, [95,98,139,140,99,101,[124][125][126][127]133,134] TiO 2 . [100,102,[136][137][138][141][142][143][144][145][146]103,104,[128][129][130][131][132]135] These materials have been demonstrated as effective antibacterial coatings.…”
Section: Inorganic Materials Interacting With Microorganismsmentioning
confidence: 99%